BI O MEC HA NICS IN CAR VING CUR VE OF AL PI NE SKI ING - Rašid Hadžić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
Ba sic goal of this work is to ex pla in dyna mic ba lan ce on exam ple of pa ral lel curving cur ve re gar ding pla ce and ti me of sho wing and ba sic ski ing mo ve ments du ring a cur ve per for ming